Thinking clearly : a guide to critical reasoning - LeBlanc, Jill E. (New York : W. W. Norton, 1998)
Identifying arguments. Standardizing arguments. Categorical logic. Necessary and sufficient conditions. Language. Accepting premises. Relevance. Arguments from analogy. Arguments from experience. Causal arguments.
Keywords: Logic; Critical thinking; Critical thinking; Logic